UJI EFEKTIFITAS Aloe vera TERHADAP PERTUMBUHAN Salmonella typhi SECARA IN VITRO - Erni Yohani Mahtuti (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2022)
Aloe vera has many health benefits, containing saponins, aloin anthraquinone complex, barbaloin, isobarbaloin, athranol, aloemodin, cinnamic acid, chrysophanic acid, reistanol and essential oils. The aim of the study was to determine the effect of Aloe vera extract on the growth of Salmonella typhi bacteria. Research is experimental. Research Methods with Kirby Bouer. Concentrations were 100%, 70% and 50% with chloramphenicol control on Muller Hinton media. The results of the study based on the growth inhibition zone of Salmonella typhi with a minimum concentration of 50% have shown the ability to inhibit bacterial growth with the results of inhibition zones of each concentration of 50% of the inhibition zone being 7 ± 0.66 mm, 70% : 8.4 ± 0.38 and 100% : 12 ± 0.65. Inhibition zone of control : 22.58 ± 0.28. Aloe vera has the ability to inhibit the growth of Salmonella typhi in vitro